Triazolopyridine ethers as potent, orally active mGlu2 positive allosteric modulators for treating schizophrenia. Issue 2 (15th January 2017) - Higgins, Mendi A.; Marcin, Lawrence R.; Christopher Zusi, F.; Gentles, Robert; Ding, Min; Pearce, Bradley C.; Easton, Amy; Kostich, Walter A.; Seager, Matthew A.; Bourin, Clotilde; Bristow, Linda J.; Johnson, Kim A.; et al.
Graphical abstract: Abstract: Triazolopyridine ethers with mGlu2 positive allosteric modulator (PAM) activity are disclosed. The synthesis, in vitro activity, and metabolic stability data for a series of analogs is provided. The effort resulted in the discovery of a potent, selective, and brain penetrant lead molecule BMT-133218 ((+)-7m ). After oral administration at 10 mg/kg, BMT-133218 demonstrated full reversal of PCP-stimulated locomotor activity and prevented MK-801-induced working memory deficits in separate mouse models. Also, reversal of impairments in executive function were observed in rat set-shifting studies at 3 and 10 mg/kg ( p.o .). Extensive plasma protein binding as the result of high lipophilicity likely limited activity at lower doses. Optimized triazolopyridine ethers offer utility as mGlu2 PAMs for the treatment of schizophrenia and merit further preclinical investigation.